Pocket world in figures 2010 (London, 2010)
The 2010 edition has been completely updated, revised, refreshed and expanded. As regulars will know, The Economist Pocket World in Figures contains rankings on numerous topics in subject areas as wide-ranging as geography, population, business, the economy, trade, transport, finance, industry, demographics, the environment, society, culture and crime. If you want to know: * the highest mountain or longest river * where economic growth is fastest or inflation is highest * who consumes the most energy * where innovation is highest * where computer and mobile phone ownership is highest * which countries have the most asylum seekers * who spends most, and who the least, on healthcare * the heaviest drinkers and smokers * who recycles most * facts about obesity this annual bestseller has the answers to all these questions and more. It now contains facts on more than 200 topics, data on more than 180 countries and profiles of more than 65 of the world's major economies, together with special profiles on the Euro Zone and the World. No well-informed person can afford to be without it.
Keywords: Economics